Gender Effect on Views of Wisdom and Wisdom Levels - Xiong, Mimi; Wang, Fengyan (Frontiers in Psychology, 2021)
Gender differences in wisdom are an important theme in mythology, philosophy, psychology, and daily life. Based on existing psychological research, consensus and dispute exist between the two genders on the views of wisdom and in levels of wisdom. In terms of the views of wisdom, the way men and women view wisdom is highly similar, and, from the perspectives of both ordinary people and professional researchers of wisdom psychology, wise men and women are extremely similar. Regarding wisdom level, research has revealed that, though significant gender effects exist in the level of overall wisdom, reflective and affective dimension, and interpersonal conflict coping styles, the effect sizes were small, which indicated that these gender differences were not obvious. It would be desirable for future research to combine multiple wisdom measurements, strengthen research on the psychological gender effect of wisdom, focus on the moderating role of age on the relationship between wisdom and gender.